2021
DOI: 10.1038/s41467-021-25708-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced gliomas represent H3-/IDH-wild type pediatric gliomas with recurrent PDGFRA amplification and loss of CDKN2A/B

Abstract: Long-term complications such as radiation-induced second malignancies occur in a subset of patients following radiation-therapy, particularly relevant in pediatric patients due to the long follow-up period in case of survival. Radiation-induced gliomas (RIGs) have been reported in patients after treatment with cranial irradiation for various primary malignancies such as acute lymphoblastic leukemia (ALL) and medulloblastoma (MB). We perform comprehensive (epi-) genetic and expression profiling of RIGs arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 70 publications
(92 reference statements)
4
49
0
1
Order By: Relevance
“…[6] Recent molecular analysis suggested that RIGs harbor a largely homogeneous genetic and epigenetic pro le of sporadic pediatric receptor tyrosine kinase I GBM, which could be particularly vulnerable to ionizing radiation. [13,14] These clinical and molecular evidences support the use of ReRT in the treatment of RIG. Further studies are needed to con rm the e cacy of ReRT in a large cohort.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…[6] Recent molecular analysis suggested that RIGs harbor a largely homogeneous genetic and epigenetic pro le of sporadic pediatric receptor tyrosine kinase I GBM, which could be particularly vulnerable to ionizing radiation. [13,14] These clinical and molecular evidences support the use of ReRT in the treatment of RIG. Further studies are needed to con rm the e cacy of ReRT in a large cohort.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, it also reminded us of the potential risk of developing RIG after radiation therapy for diffuse gliomas and the importance of long-term followup. Prior studies consistently report that RIG does not harbor IDH1/2 mutations [11][12][13], therefore, identifying the wild-type IDH1/2 is diagnostic relevant. We recommend evaluating IDH1/2 mutation status between the primary and secondary gliomas, especially in cases with recurrent glioma occurring long time after successful initial treatment.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations